Miami classification for probe-based confocal laser endomicroscopy - Wallace, M.; Lauwers, G. Y.; Chen, Y.; Dekker, E.; Fockens, P.; Sharma, P.; Meining, A. (Endoscopy, 2011)
An essential element for any new advanced imaging technology is standardization of indications, terminology, categorization of images, and research priorities. In this review, we propose a state-of-the-art classification system for normal and pathological states in gastrointestinal disease using probe-based confocal laser endomicroscopy (pCLE). The Miami classification system is based on a consensus of pCLE users reached during a meeting held in Miami, Florida, in February 2009.